“I Asked the Dog to Sniff at All my Birth-Marks”: The Child from Donations by Justyna Bargielska - Czyżak, Agnieszka (Porównania, 2021)
The article contains critical considerations devoted to the poetry written by Justyna Bargielska, especially to her lyric volume Dziecko z darów (The child from donations) published in 2019. The important context of those resolving remains the posthumanism, conceived as an open set of different ideas connected by non-anthropocentric perspective of inquiries. In Bargielska’s poetry, the new way of portraying animals and their relations to the people is associated with visions of an approaching global catastrophe and the end of mankind.